Knowledge building in teacher professional learning communities: Focus of meeting matters. (October 2016) - Popp, Jacquelynn S.; Goldman, Susan R.
Abstract: Professional learning communities (PLCs) of teachers have potential as powerful professional development contexts. However, efforts to characterize and document teacher PLCs suggest that productive learning is the exception rather than the rule. This mixed methods case study derived indicators of knowledge building discourse and examined their prevalence in nine PLC meetings among English Language Arts teachers within the same school (3 grade band teams x 3 meetings each). Analyses indicated significantly more knowledge building in meetings focused on assessment systems as compared to meetings focused on instructional practices. Implications for ways in which PLCs could foster knowledge building are discussed. Highlights: Knowledge building indicators in teacher PLC meetings were assessed. Meetings where teachers discussed assessment systems showed more knowledge building. Meetings where teachers discussed their instruction showed little knowledge building. Interactivity and inquiry stance were more evident in assessment than instruction meetings.